2017
DOI: 10.5812/zjrms.11773
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Self-Compassion in the Relationship Between Anxiety and Procrastination

Abstract: Background: Procrastination is common among students. There are inconsistent evidence indicating the relationship between anxiety and procrastination. Similarly, underlying mechanisms of this relationship is not fully understood. One of these mechanisms may be self-compassion that may counteracts the negative effects of anxiety and procrastination. Hence, this research is aimed at investigating the mediating role of self-compassion in the relationship between anxiety and procrastination. Methods: This cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…At the same time, the fact that the age of the subjects correlated positively with two variables of the study (subjective wellbeing, and academic performance) and negatively with the other two study variables (cognitive test anxiety, and academic procrastination) indicates that in adolescence, and especially in girls, attention should be focused on managing anxiety evaluation and procrastination. The study's results confirm, in agreement with other studies ( 19 , 27 ), that procrastination correlates positively with test anxiety, while test anxiety correlates negatively with academic performance ( 43 ). So, given the negative effect of procrastination/ postponement on academic performance and wellbeing ( 5 , 11 – 19 ) academic procrastination must be discouraged by building positive, collaborative, and effective learning environments ( 67 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At the same time, the fact that the age of the subjects correlated positively with two variables of the study (subjective wellbeing, and academic performance) and negatively with the other two study variables (cognitive test anxiety, and academic procrastination) indicates that in adolescence, and especially in girls, attention should be focused on managing anxiety evaluation and procrastination. The study's results confirm, in agreement with other studies ( 19 , 27 ), that procrastination correlates positively with test anxiety, while test anxiety correlates negatively with academic performance ( 43 ). So, given the negative effect of procrastination/ postponement on academic performance and wellbeing ( 5 , 11 – 19 ) academic procrastination must be discouraged by building positive, collaborative, and effective learning environments ( 67 ).…”
Section: Discussionsupporting
confidence: 92%
“…There are factors that cause anxiety among students correlated with academic performance, namely peer acceptance, uncertainty about the nature of expected demands, and their ability to meet these demands ( 9 ), doubts about their intellectual capacities, their time management capacities ( 37 , 38 ), insufficiently defined institutional standards for marking quality items, concerns about the fairness of certain types and assessment tools (e.g., across studies undertaken, students reported that oral presentations and high-stakes written assignments caused them more anxiety) ( 39 ). The range of anxiety-generating factors also includes the parenting style faced by the student ( 40 42 ), the negative, repetitive thinking about the consequences of failure that can lead to self-judgment and over-identification ( 10 , 43 ). It should be emphasized that all these factors are added to those generated by learning in open spaces, as a result of online education ( 44 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of procrastination has reported up to 95% among students (1). Procrastination results in the decrease of academic performance (2), and on the other hand, it is related to anxiety (3). While procrastination is used to avoid unpleasant consequences, and as a result is considered as an emotion regulation (4), studies show that procrastination can lead to a significant increase in distress (5).…”
Section: Introductionmentioning
confidence: 99%
“…Procrastinators expe-rience lower acceptance of themselves (14). A study investigated the relation between procrastination and anxiety, considering self-compassion as a mediator (3). Another research investigated the relationship between anxiety and acceptance in Iranian students (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation